Alterations of the White Matter in Patients With Knee Osteoarthritis: A Diffusion Tensor Imaging Study With Tract-Based Spatial Statistics - Cheng, Shirui; Dong, Xiaohui; Zhou, Jun; Tang, Chenjian; He, Wenhua; Chen, Yang; Zhang, Xinyue; Ma, Peihong; Yin, Tao; Hu, Yimei; Zeng, Fang; Li, Zhengjie; et al. (Frontiers in Neurology, 2022)
Background Functional and structural alterations in the gray matter have been observed in patients with knee osteoarthritis (KOA). However, little is known about white matter changes in KOA. Here, we evaluated fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) to investigate potential alterations in the white matter of patients with KOA. Methods A total of 166 patients with KOA, along with 88 age- and sex-matched healthy controls were recruited and underwent brain magnetic resonance imaging (MRI). Diffusion tensor imaging (DTI) data were collected and analyzed using tract-based spatial statistics (TBSS). Statistical significances were determined at p < 0.05 and were corrected by the threshold-free cluster enhancement (TFCE) method. Then, we evaluated potential correlations between FA, MD, AD, RD values and disease duration, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, and visual analog scale (VAS) scores. Results FA values for the body of corpus callosum, splenium of corpus callosum, bilateral superior longitudinal fasciculus, cingulum, bilateral superior corona radiata, and right posterior corona radiata were significantly higher in patients with KOA than in healthy controls (p < 0.05, TFCE corrected). Compared with healthy controls, patients with KOA also had significantly lower MD, AD, and RD values of the genu of corpus callosum, body of corpus callosum, splenium of corpus callosum, corona radiata, right posterior thalamic radiation, superior longitudinal fasciculus, and middle cerebellar peduncle (p < 0.05, TFCE corrected). Negative correlations were detected between WOMAC scores and AD values for the body of the corpus callosum and the splenium of the corpus callosum (p < 0.05, FDR corrected). Conclusion Patients with KOA exhibited extensive white matter alterations in sensorimotor and pain-related regions. Longitudinal observation studies on the causation between abnormalities in the white matter tracts and KOA is needed in the future.